2020
DOI: 10.1177/1178636120945294
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation in Laboratory-Bred Mice: An In Vivo Assay on Gut Microbiome and Body Weight

Abstract: Saudi Arabia is in a tropical geographical region with a population that has access to adequate diet. There is, however, a high level of vitamin D deficiency in the Kingdom, comorbid with other disease. There is the postulation of a correlation between a healthy gut microbiota and balanced levels of serum vitamin D. This investigation looks into the effect of vitamin D supplementation on the gut flora of laboratory-bred mice as well as any possible association on body weight. BALB/C mice weighing between 34 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…The animals were further stratified to three different dietary vitamin D intakes (within the chow background): low (100 IU/kg diet), normal (1000 IU/kg diet), and high (5000 IU/kg diet). The doses of vitamin D were based on literature review of mouse models utilizing various vitamin D concentrations to achieve dose-dependent physiologic changes in vitamin D but prevent hypo/hypercalcemia from occurring [32][33][34][35]. The vitamin D doses were also chosen to mimic standard treatment doses in humans for vitamin D deficiency without causing vitamin D toxicity.…”
Section: Dietmentioning
confidence: 99%
“…The animals were further stratified to three different dietary vitamin D intakes (within the chow background): low (100 IU/kg diet), normal (1000 IU/kg diet), and high (5000 IU/kg diet). The doses of vitamin D were based on literature review of mouse models utilizing various vitamin D concentrations to achieve dose-dependent physiologic changes in vitamin D but prevent hypo/hypercalcemia from occurring [32][33][34][35]. The vitamin D doses were also chosen to mimic standard treatment doses in humans for vitamin D deficiency without causing vitamin D toxicity.…”
Section: Dietmentioning
confidence: 99%
“…Badger-Emeka et al reported that different doses of vitamin D can influence the body weight and gut microbial colonies in mice. The authors found decreased gut Salmonella/Shigella and E. coli colonies under low- and normal-dose vitamin D. However, P. aeruginosa was significantly decreased under high vitamin D doses [ 88 ].…”
Section: Saudi Arabian Microbiome Studies On Human Healthmentioning
confidence: 99%